2017
DOI: 10.22178/pos.27-4
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Their Teachers’ Performance in Teaching Engineering Drawing in Nigerian Tertiary Institutions

Abstract: Abstract. There have been concerns about the performance of Nigerian school teachers' in delivering occupational related courses. However, there are currently limited empirical data on this phenomenon -in particular with respect to the teaching of engineering drawing -to justify further actions from educational managers and policy makers. The aim of this study was to assess teachers' performance in teaching engineering drawing using students' perception as indicator of teachers' performance. The study utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Then various approaches can be developed to assess and evaluate teacher performance. Hassan, Alias, Saleh, & Awang (2017), involving engineering teachers, investigated the teacher performance which can be assessed from students' perception. Further, Lee, Lam, & Li (2003) described how far the learning process' effectiveness and evaluation on the teacher's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Then various approaches can be developed to assess and evaluate teacher performance. Hassan, Alias, Saleh, & Awang (2017), involving engineering teachers, investigated the teacher performance which can be assessed from students' perception. Further, Lee, Lam, & Li (2003) described how far the learning process' effectiveness and evaluation on the teacher's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Defining the characteristics of a good project [39], noted that, a project must have clear aims and objectives which is mostly aimed at solving a problem; it must involve needs analysis; involve one or more solutions aimed at bringing lasting change; must have achievable aims based on the available resources; must have a time frame in terms of place and context; must be complex enough and involve skills planning and implementation as well as execution players and partners; projects is a collective task involving a team of various participants who must work collaboratively; project are unique as every project is termed from new problems, challenges, and ideas; project is an adventure with various risk and uncertainty; project can be assessed by planning and analyses bases on aims which must be subjected to evaluation iii. Teamwork: Literature findings have revealed that, the success of POBL depends on teamwork [16], [20], [22], [23], [32], [40], [41]. [24], describes teamwork as someplace students "read, discuss, diagnose, and also check out ways to resolve the problem".…”
Section: Project: Project Learning Approach Was Introduced Inmentioning
confidence: 99%
“…The role of students in the instructional process is critical as their perception could influence their attitude toward technical drawing or any other technical education subjects [4]. Perception is the way people judge others with who they are in contact [2].…”
Section: Introductionmentioning
confidence: 99%
“…Perception is the way people judge others with who they are in contact [2]. Generally, students usually judge their school teachers in areas such as the teachers' knowledge of the subject matter, communication ability, the choice of appropriate teaching method and the general classroom management skills [4]. A teacher who is rated on these indices at high level is likely to enjoy the confidence, respect and admiration of his students based on their perception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation